Anti-HSV activity of Hypnea musciformis cultured with different phytohormones - Mendes,Gabriella da Silva (2012)
Four extracts from the seaweed Hypnea musciformis (Wulfen in Jacq.) J.V. Lamour. (Rhodophyta), collected directly from its natural habitat or cultivated in the presence of phytohormones, were evaluated for their ability to inhibit the replication of acyclovir-resistant herpes simplex viruses types 1 (HSV-1) and 2 (HSV-2) strains. The main purpose was to determinate whether these growth conditions would affect the antiviral activity. Our results showed the possibility of improving the anti-HSV activity by using extracts from algae cultured in the presence of phytohormones.